1995
DOI: 10.1172/jci117926
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of diabetic nephropathy in db/db mice with glycated albumin antagonists. A novel treatment strategy.

Abstract: Accelerated protein glycation in diabetes has been mechanistically linked to the pathogenesis of diabetic nephropathy. Because glycated albumin induces abnormalities in cultured mesangial cells that resemble those characterizing the glomerular mesangium in diabetes, and monoclonal antibodies (A717) specific for Amadori-modified glycated albumin prevent these abnormalities, we postulated that in vivo administration of A717 could retard the progression of diabetic nephropathy. To test this hypothesis, diabetic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
93
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(101 citation statements)
references
References 54 publications
8
93
0
Order By: Relevance
“…In the present study, ZDF-fa/fa rats showed significant renal hypertrophy compared with lean rats as early as 3 months of age. The levels of fibronectin, collagen type IV, and VEGF mRNA in the kidney were elevated in ZDF-fa/fa rats, as previously reported in other models of diabetes (Cohen et al, 1995;Tsuchida et al, 1999). In addition, ZDF-fa/fa rats showed a transient increase in GFR level in the early to middle stages of the disease, with glomerular hypertrophy indicating the presence of hyperfiltration.…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, ZDF-fa/fa rats showed significant renal hypertrophy compared with lean rats as early as 3 months of age. The levels of fibronectin, collagen type IV, and VEGF mRNA in the kidney were elevated in ZDF-fa/fa rats, as previously reported in other models of diabetes (Cohen et al, 1995;Tsuchida et al, 1999). In addition, ZDF-fa/fa rats showed a transient increase in GFR level in the early to middle stages of the disease, with glomerular hypertrophy indicating the presence of hyperfiltration.…”
Section: Discussionsupporting
confidence: 84%
“…Given the recent studies reporting that AGEs and RAGE are involved in diabetic nephropathy, several methods have been developed to cure chronic kidney disease by interfering with the pathophysiological effect of AGE (12). Accumulation of collagen and secretion of renal profibrotic cytokines could be reduced by preventing AGE formation or blocking RAGE-dependent signaling (17,18). Blocking RAGE-amphoterin decreases growth and metastases of tumors by suppressing p44/p42, p38, and SAP/JNK MAPK signaling in cancer cells (19).…”
Section: Autosomal Dominant Polycystic Kidney Disease (Adpkd)mentioning
confidence: 99%
“…The precipitate was crystallized from dioxane/methanol (1:1), and oxalate was replaced by chloride by anion exchange chromatography. Fructosyl propylamine in reduced form was prepared as follows; 1.2 g of NaBH 4 was added to 200 mg of fructosyl propylamine dissolved in 50 ml of water and incubated 12 h at room temperature. 1 ml of acetic acid was added to stop the reaction, and the solvent was removed under reduced pressure.…”
Section: Synthesis Of Glycated Substratesmentioning
confidence: 99%
“…The Amadori product, which forms in the initial stages of the Maillard reaction in vivo, has been shown to be recognized by receptors at the surface of monocytes, aortic endothelial, and mesangial cells (1)(2)(3), and treatment of diabetic mice with antibodies to glycated albumin decreases the rate of progression of diabetic nephropathy (4). Amadori products of glucose are precursors of the glycoxidation products pentosidine and N ⑀ -(carboxymethyl)lysine (5-7), which are elevated in diabetes and the levels of which increase with the severity of diabetic complications (8 -10).…”
mentioning
confidence: 99%